Estimating Food Additive Intake: A Systematic Review of Intake and Nonlaboratory Methodologies - Samantha A. Hall; Gina L. Trakman (Food Frontiers, 2025)
ABSTRACT Despite increasing interest in the physiological and health effects of select additives (e.g., artificial food colors, emulsifiers, flavor enhancers, and preservatives), it is unclear whether there is a preferred nonlaboratory methodology for measuring additive intake in humans (milligrams of additive per kilogram of bodyweight [mg/kg bw]). This paper serves to review the current literature and summarize the mean additive consumption of study participants. A systematic review was performed by searching CINAHL, Medline, ProQuest, Scopus, and Web of Science from January 1, 2015 to January 1, 2024 to synthesize studies assessing additive intake among humans (mg/kg bw) using nonlaboratory methodologies. Reference lists of included studies were also reviewed. A total of 21 studies from 12 countries were identified, with a combined population pool of more than 366,297 participants. Food intake assessment methodologies used included 24‐h recall (n = 11), food frequency questionnaires (n = 6), and food diaries (n = 4), combined with additive data from manufacturer databases (n = 18), chemical food analysis (n = 11), and food label surveys (n = 11). Among assessed populations, only 2.2% of additive intake values (n = 3) were found to be consumed above the ADI (Allura Red AC, Erythrosine, and Sunset Yellow FCF). No preferred additive intake methodology was identified, with methodologies dependent on available data, resourcing, and the population being assessed. The inclusion of quantifiable additive data on food labels would facilitate further research in humans and, if required, allow consumers to make choices regarding additive intake.